Bioanalytical Method for Simultaneous Quantification of Itraconazole and Atorvastatin in Human Plasma - Bodiwala, Kunjan B.; Pujara, Flora J.; Khadela, Avinash D.; Savale, Shrinivas S. (Drug Metabolism and Bioanalysis, 2025)
<span class=
Keywords: atorvastatin calcium